Composite current collector and preparation method and application thereof
By applying the functional layer of the epoxy resin-flame retardant functional compound on the current collector of the sodium ion battery, the problem of poor adhesion between the current collector and the hard carbon negative electrode is solved, and the peeling force and safety performance of the battery are improved.
Patent Information
- Application Number
- CN202411775521.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-04
- Publication Date
- 2025-03-21
- Estimated Expiration
- 2044-12-04
AI Technical Summary
In existing sodium ion batteries, the bonding of the current collector and the hard carbon negative electrode is poor, resulting in a decrease in the first-time efficiency, rapid cycle life attenuation, and safety hazards.
The composite liquid collector is used, including a current collector substrate and a functional layer, and the functional layer contains epoxy resin-flame retardant functional compounds. By introducing epoxy resin-flame retardant functional compounds into the functional layer, the adhesive performance of the current collector and the negative electrode material is improved and the safety performance of the battery is improved.
The adhesion between the current collector and the active layer is significantly improved, the peeling force of the negative electrode is improved, the Hi-pot defect rate is reduced, and the safety performance of the battery is enhanced.
Smart Images

Figure BDA0005173337770000031 
Figure BDA0005173337770000081 
Figure BDA0005173337770000151
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of batteries, and in particular to a composite current collector, a preparation method thereof, and an application thereof. Background Art
[0002] In sodium-ion batteries, current collectors are typically used at the positive and negative electrodes to carry the current. As the structure or component that collects the current, current collectors must not only possess high conductivity but also possess a range of properties, including lightweight, mechanical strength, high electrode peeling resistance, and safety. Currently, aluminum foil is commonly used as the current collector.
[0003] Hard carbon anodes have a large surface area, but this increases their adhesion to foil, making them prone to powder loss. Furthermore, during the manufacturing process, poor adhesion between the current collector and the anode material increases the proportion of high-pot failures, leading to lower initial efficiency and rapid cycle life degradation. Furthermore, when a battery cell fails, the hard carbon anode is highly flammable, causing the current collector to melt, raising safety concerns.
[0004] Therefore, providing a current collector that can improve its bonding performance with the negative electrode and enhance the safety performance of the battery is a technical problem that needs to be solved urgently. Summary of the Invention
[0005] In view of the above technical problems existing in the prior art, the purpose of the present invention is to provide a composite current collector and its preparation method and application.
[0006] To achieve the above object, the present invention adopts the following technical solutions:
[0007] In a first aspect, the present invention provides a composite current collector comprising a current collector substrate and a functional layer disposed on at least one surface of the current collector substrate, wherein the functional layer comprises a binder composition comprising an epoxy resin-flame retardant functional compound.
[0008] The following are preferred technical solutions of the present invention, but are not intended to limit the technical solutions provided by the present invention. Through the following preferred technical solutions, the technical objectives and beneficial effects of the present invention can be better achieved and realized.
[0009] Preferably, the epoxy resin-flame retardant functional compound is an epoxy resin-fluorobenzene compound.
[0010] Preferably, the thickness of the functional layer is 1 μm to 3 μm, for example, 1 μm, 1.2 μm, 1.4 μm, 1.5 μm, 1.6 μm, 1.8 μm, 2 μm, 2.3 μm, 2.5 μm, 2.6 μm, 2.8 μm or 3 μm.
[0011] In a second aspect, the present invention provides a method for preparing the composite current collector according to the first aspect, the method comprising the following steps:
[0012] (1) After introducing nitro groups into the flame retardant material, a flame retardant material having nitro groups is obtained, and the flame retardant material having nitro groups is mixed with an epoxy resin and subjected to an esterification reaction to obtain a binder composition;
[0013] (2) mixing the binder composition with a curing agent and a solvent to obtain a functional slurry;
[0014] (3) The functional slurry is coated on the surface of the current collector substrate and dried to obtain a composite current collector.
[0015] Preferably, the epoxy resin in step (1) comprises at least one of bisphenol diglycidyl ester, diphenol propane and polyphenol type glycidyl ester.
[0016] Preferably, the flame retardant material in step (1) comprises a fluorobenzene compound.
[0017] Preferably, the fluorobenzene compound includes at least one of fluorobenzene, difluoroaniline, trifluoroaniline and tetrafluorophenol.
[0018] As a preferred technical solution of the preparation method of the present invention, the method of introducing nitro groups into the flame retardant material in step (1) is: mixing the flame retardant material, a catalyst and concentrated nitric acid to allow the flame retardant material to undergo a nitration reaction with the nitric acid.
[0019] Preferably, the nitration reaction is carried out with stirring.
[0020] Preferably, the flame retardant material, catalyst and concentrated nitric acid are mixed for 30 to 60 minutes.
[0021] Preferably, the temperature of the nitration reaction is 40°C to 70°C.
[0022] Preferably, the pressure of the nitration reaction is controlled within the range of 1 MPa to 3 MPa.
[0023] Preferably, the catalyst comprises concentrated sulfuric acid.
[0024] Preferably, the mass ratio of the flame retardant material, the catalyst and concentrated nitric acid is (3-8):(3-8):(3-8).
[0025] As a preferred technical solution of the preparation method of the present invention, in step (2), the material for mixing with the binder composition further includes a conductive agent;
[0026] In parts by mass, the content of each material is:
[0027]
[0028] Preferably, the curing agent includes at least one of diaminodicyclohexylmethane, triethylene glycol amine, boron trifluoride glycerol and boron trifluoride aniline.
[0029] Preferably, the conductive agent includes at least one of graphite, Super P, carbon nanotubes, acetylene black and Ketjen black.
[0030] Preferably, the solvent includes at least one of alcohol, water, acetone, NMP, ethyl ester, and 50% ethanol.
[0031] Preferably, the alcohol comprises methanol and / or ethanol.
[0032] Preferably, the mass fraction of the alcohol is 40% to 60%.
[0033] In a second aspect, the present invention provides a negative electrode sheet, comprising a current collector and an active layer arranged on at least one side surface of the current collector, wherein the current collector is the composite current collector described in the first aspect, or the composite current collector obtained by the preparation method described in the second aspect.
[0034] Preferably, the active layer includes a negative electrode active material, and the negative electrode active material includes hard carbon.
[0035] Preferably, the peeling force of the negative electrode sheet is greater than 0.8N.
[0036] In a third aspect, the present invention provides a battery comprising the negative electrode sheet described in the second aspect.
[0037] Preferably, the battery is a sodium ion battery.
[0038] Compared with the prior art, the present invention has the following beneficial effects:
[0039] (1) The present invention introduces an epoxy resin-flame retardant functional compound into the functional layer and utilizes the functional layer to modify the current collector substrate. The epoxy resin-flame retardant functional compound has the effects of modification and curing. The epoxy group therein has excellent adhesion properties to metal materials such as aluminum, iron, and copper, greatly improving the adhesion between the current collector and the active layer, thereby improving the peeling force of the negative electrode and reducing the Hi-pot defect rate when preparing the electrode sheet. At the same time, the flame retardant component in the epoxy resin-flame retardant functional compound is flame retardant, which can prevent the foil from melting and causing safety problems when the battery cell fails.
[0040] (2) The preparation method of the composite current collector provided by the present invention is simple and easy to implement in industrial production. DETAILED DESCRIPTION
[0041] The technical solution of the present invention is further illustrated below through specific implementation methods.
[0042] In one embodiment, the present invention provides a composite current collector, comprising a current collector substrate and a functional layer disposed on at least one surface of the current collector substrate, wherein the functional layer comprises a binder composition comprising an epoxy resin-flame retardant functional compound.
[0043] In the present invention, the epoxy resin-flame retardant functional compound is a compound formed by chemical reaction between epoxy resin and flame retardant material, wherein epoxy resin molecules are uniformly distributed on the molecular chain of the flame retardant component (such as fluorobenzene).
[0044] In one embodiment, the present invention introduces an epoxy resin-flame-retardant functional compound into the functional layer, which is then used to modify the current collector substrate. The epoxy resin-flame-retardant functional compound has the effects of modification and curing. The epoxy groups therein have excellent adhesion to metal materials such as aluminum, iron, and copper, greatly improving the adhesion between the current collector and the active layer, thereby increasing the peel force of the negative electrode and reducing the Hi-pot defect rate when preparing the electrode sheet. At the same time, the flame-retardant component in the epoxy resin-flame-retardant functional compound is flame-retardant, which can prevent the foil from melting and causing safety issues when the battery cell fails.
[0045] It should be noted that the epoxy resin-flame retardant functional compound in the present invention cannot be replaced by a mixture of epoxy resin and flame retardant material, otherwise excellent modification and curing effects cannot be achieved.
[0046] In summary, the composite current collector provided by one embodiment of the present invention can improve the adhesion between the current collector and the active layer, increase the peeling force of the negative electrode, reduce the Hi-pot defect rate when preparing the electrode sheet, and also improve the safety performance of the battery cell, which is conducive to promoting the commercial development of sodium-ion batteries.
[0047] In one embodiment, the epoxy resin-flame retardant functional compound is an epoxy resin-fluorobenzene compound.
[0048] In one embodiment, the thickness of the functional layer is 1 μm to 3 μm, for example, 1 μm, 1.2 μm, 1.4 μm, 1.5 μm, 1.6 μm, 1.8 μm, 2 μm, 2.3 μm, 2.5 μm, 2.6 μm, 2.8 μm, or 3 μm. If the thickness of the functional layer is too small, it will be detrimental to the process and will easily lead to thickness fluctuations, which will in turn lead to a decrease in the peeling force between the current collector and the active layer. If the thickness of the functional layer is too large, the peeling force will be reduced, powder will easily fall off, and the Hi-pot test failure rate will increase, which is not conducive to the high capacity and high energy density of the battery.
[0049] In another embodiment, the present invention provides a method for preparing the composite current collector as described above, the method comprising the following steps:
[0050] (1) After introducing nitro groups into the flame retardant material, a flame retardant material having nitro groups is obtained, and the flame retardant material having nitro groups is mixed with an epoxy resin and subjected to an esterification reaction to obtain a binder composition;
[0051] (2) mixing the binder composition with a curing agent and a solvent to obtain a functional slurry;
[0052] (3) The functional slurry is coated on the surface of the current collector substrate and dried to obtain a composite current collector.
[0053] In the present invention, the nitro group on the flame retardant material and the epoxy group of the epoxy resin can undergo an esterification reaction, thereby forming the adhesive composition.
[0054] The preparation method of the composite current collector provided in one embodiment of the present invention has a simple process and is easy to implement in industrial production.
[0055] In one embodiment, the epoxy resin in step (1) includes at least one of bisphenol diglycidyl ester, diphenol propane and polyphenol glycidyl ester.
[0056] In one embodiment, the flame retardant material in step (1) comprises a fluorobenzene compound.
[0057] In one embodiment, the fluorobenzene compound includes at least one of fluorobenzene, difluoroaniline, trifluoroaniline and tetrafluorophenol.
[0058] Fluorobenzene has a certain lubricity, which can optimize the lubricity of the binder composition and prevent the surface of the active layer from being too rough, thereby having better processing performance. For example, if the surface of the active layer is too rough, it will easily lead to wrinkling of the pole piece due to the roughness during the winding process of the battery cell.
[0059] In one embodiment, the method of introducing nitro groups into the flame retardant material in step (1) is: mixing the flame retardant material, a catalyst and concentrated nitric acid, so that the flame retardant material and the nitric acid undergo a nitration reaction.
[0060] In one embodiment, the nitration reaction is accompanied by stirring.
[0061] In one embodiment, the flame retardant material, catalyst and concentrated nitric acid are mixed for 30 to 60 minutes, for example, 30 minutes, 35 minutes, 40 minutes, 45 minutes, 50 minutes, 55 minutes or 60 minutes.
[0062] In one embodiment, the temperature of the nitration reaction is 40°C to 70°C, for example, 40°C, 42°C, 45°C, 47°C, 50°C, 53°C, 55°C, 58°C, 60°C, 62°C, 65°C, 67°C or 70°C.
[0063] In one embodiment, the pressure of the nitration reaction is controlled within the range of 1 MPa to 3 MPa. For example, the pressure may be 1 MPa, 1.2 MPa, 1.5 MPa, 1.7 MPa, 2 MPa, 2.2 MPa, 2.4 MPa, 2.6 MPa, 2.8 MPa or 3 MPa.
[0064] In one embodiment, the catalyst comprises concentrated sulfuric acid.
[0065] In one embodiment, the mass fraction of concentrated sulfuric acid is 65% to 98%, for example, it can be 65%, 66%, 68%, 70%, 73%, 76%, 78%, 80%, 82%, 85%, 88%, 90%, 92%, 93%, 95%, 96%, 97% or 98%, etc.
[0066] In one embodiment, the mass ratio of the flame retardant material, the catalyst and the concentrated nitric acid is (3-8):(3-8):(3-8), wherein the selection range of the flame retardant material is "3-8", for example, it can be 3, 3.5, 4, 4.5, 5, 5.5, 6, 6.5, 7, 7.5 or 8, etc.; the selection range of the catalyst is "3-8", for example, it can be 3, 3.5, 4, 4.5, 5, 5.5, 6, 6.5, 7, 7.5 or 8, etc.; the selection range of concentrated nitric acid is "3-8", for example, it can be 3, 3.5, 4, 4.5, 5, 5.5, 6, 6.5, 7, 7.5 or 8, etc.
[0067] In one embodiment, the mass fraction of concentrated nitric acid is 60% to 88%, for example, it can be 60%, 62%, 63%, 64%, 65%, 66%, 67%, 68%, 70%, 72%, 75%, 77%, 80%, 82%, 83%, 84%, 86% or 88%, etc.
[0068] In one embodiment, the flame retardant material having a nitro group is mixed with the epoxy resin while stirring.
[0069] In one embodiment, the mixing time of the flame retardant material having a nitro group and the epoxy resin is 180 min to 240 min, for example, it can be 180 min, 185 min, 190 min, 195 min, 200 min, 205 min, 210 min, 215 min, 220 min, 225 min, 230 min or 240 min.
[0070] In one embodiment, the flame retardant material having a nitro group is mixed with the epoxy resin at room temperature.
[0071] In the present invention, room temperature refers to 23°C to 27°C, for example, it may be 23°C, 24°C, 25°C, 26°C or 27°C.
[0072] In one embodiment, in step (2), the material for mixing with the binder composition further includes a conductive agent;
[0073] In parts by mass, the content of each material is:
[0074] 10 to 24 parts epoxy resin
[0075]
[0076] In the above embodiment, the content of epoxy resin is 10 parts to 24 parts, for example, it can be 10 parts, 12 parts, 13 parts, 14 parts, 15 parts, 16 parts, 17 parts, 18 parts, 19 parts, 20 parts, 21 parts, 22 parts, 23 parts or 24 parts.
[0077] In the above embodiment, the content of the flame retardant material is 3 parts to 8 parts, for example, it can be 3 parts, 3.5 parts, 4 parts, 4.5 parts, 5 parts, 5.5 parts, 6 parts, 6.5 parts, 7 parts or 8 parts.
[0078] In the above embodiment, the content of the conductive agent is 5 parts to 12 parts, for example, it can be 5 parts, 5.5 parts, 6 parts, 7 parts, 7.5 parts, 8 parts, 8.5 parts, 9 parts, 9.5 parts, 10 parts, 11 parts or 12 parts.
[0079] In the above embodiment, the content of the curing agent is 1 to 2 parts, for example, 1 part, 1.2 parts, 1.4 parts, 1.5 parts, 1.6 parts, 1.8 parts or 2 parts.
[0080] In the above embodiment, the content of the solvent is 60 parts to 70 parts, for example, 60 parts, 62 parts, 64 parts, 65 parts, 66 parts, 68 parts, or 70 parts.
[0081] In the above technical solution, by adding an excess amount of epoxy resin relative to the flame retardant material, on the one hand, the epoxy resin has active epoxy groups that have excellent adhesion properties to metal materials such as aluminum, iron, and copper; on the other hand, the epoxy groups react with the free bonds on the metal surface to form chemical bonds, which greatly improves the adhesion between the primer material and the aluminum foil, and the excess epoxy resin reacts with the current collector substrate (such as aluminum foil), thereby improving the peeling force between the functional layer and the current collector substrate.
[0082] In one embodiment, the curing agent includes at least one of diaminodicyclohexylmethane, triethylene glycol amine, boron trifluoride glycerol, and boron trifluoride aniline.
[0083] In one embodiment, the conductive agent includes at least one of graphite, Super P, carbon nanotubes, acetylene black, and Ketjen black.
[0084] In one embodiment, the solvent comprises at least one of alcohol, water, acetone, NMP, ethyl ester, and 50% ethanol.
[0085] In one embodiment, the alcohol comprises methanol and / or ethanol.
[0086] In one embodiment, the mass fraction of the alcohol is 40% to 60%, for example, 40%, 42%, 44%, 46%, 48%, 50%, 53%, 55%, 58% or 60%.
[0087] In one embodiment, in step (3), the coating method includes but is not limited to any one of spraying, blade coating or roller coating.
[0088] In one embodiment, in step (3), the drying method is to heat in an oven.
[0089] In another embodiment, the present invention provides a negative electrode sheet, comprising a current collector and an active layer disposed on at least one surface of the current collector, wherein the current collector is the composite current collector described above, or a composite current collector obtained by the above preparation method.
[0090] In one embodiment, the active layer includes a negative electrode active material, and the negative electrode active material includes hard carbon.
[0091] In one embodiment, the peeling force of the negative electrode sheet is greater than 0.8N.
[0092] In another embodiment, the present invention provides a battery, comprising the above-mentioned negative electrode sheet.
[0093] In one embodiment, the battery is a sodium ion battery.
[0094] The numerical range described in the present invention includes not only the point values listed above, but also any point values between the above numerical ranges that are not listed. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values included in the range.
[0095] The following are typical but non-limiting examples:
[0096] The "parts" in the embodiments of the present invention refer to parts by mass. The mass fraction of concentrated sulfuric acid is 70%, and the mass fraction of concentrated nitric acid is 86%.
[0097] Preparation Example 1
[0098] Provided is an epoxy resin-flame retardant functional compound, the preparation method of which comprises the following steps:
[0099] Weigh 3 parts of fluorobenzene, 3 parts of concentrated sulfuric acid, and 3 parts of concentrated nitric acid, add them to a container and stir evenly for 30 minutes. Control the temperature to 70°C and the pressure to 1 MPa. Pass argon gas into a closed environment to cause nitration reaction between fluorobenzene and nitric acid to produce a flame retardant material with nitro groups.
[0100] After the flame retardant material with nitro groups has completely reacted, the temperature is lowered to room temperature, 10 parts of bisphenol diglycidyl ester is weighed and added to the above solution, and stirred for 180 minutes to allow the epoxy groups on the bisphenol diglycidyl ester to react with the nitro groups of the flame retardant material with nitro groups, so that the flame retardant material is attached to the molecular chain of the bisphenol diglycidyl ester to obtain an epoxy resin-flame retardant functional compound.
[0101] Example 1
[0102] A composite current collector is provided, comprising a current collector substrate and a functional layer disposed on at least one surface of the current collector substrate, wherein the thickness of the functional layer is 1 μm, and the functional layer comprises a binder composition, wherein the binder composition comprises an epoxy resin-flame retardant functional compound (Preparation Example 1).
[0103] This embodiment also provides a method for preparing the composite current collector, comprising the following steps:
[0104] The epoxy resin-flame retardant functional compound of Preparation Example 1 was mixed with 5 parts of graphite, 1 part of diaminodicyclohexylmethane and 60 parts of 50% ethanol by mass, and stirred evenly. The mixture was then sprayed on the surface of the substrate and dried in an oven to obtain a composite current collector.
[0105] Preparation Example 2
[0106] Provided is an epoxy resin-flame retardant functional compound, comprising the following steps:
[0107] Weigh 6 parts of difluoroaniline, 3 parts of concentrated sulfuric acid, and 3 parts of concentrated nitric acid, add them to a container and stir evenly. Stir for 45 minutes. Control the temperature to 55°C and the pressure to 2 MPa. Pass argon gas into a closed environment to allow difluoroaniline and nitric acid to undergo a nitration reaction to produce a flame retardant material with a nitro group.
[0108] After the flame retardant material with nitro groups has completely reacted, the temperature is lowered to room temperature, 17 parts of bisphenol diglycidyl ester is weighed and added to the above solution, and stirred for 210 minutes to allow the epoxy groups on the bisphenol diglycidyl ester to react with the nitro groups of the flame retardant material with nitro groups, so that the flame retardant material is attached to the molecular chain of the bisphenol diglycidyl ester to obtain an epoxy resin-flame retardant functional compound.
[0109] Example 2
[0110] A composite current collector is provided, comprising a current collector substrate and a functional layer disposed on at least one surface of the current collector substrate, wherein the thickness of the functional layer is 2 μm, and the functional layer comprises an adhesive composition, wherein the adhesive composition comprises an epoxy resin-flame retardant functional compound (Preparation Example 2).
[0111] This embodiment also provides a method for preparing the composite current collector, comprising the following steps:
[0112] The epoxy resin-flame retardant functional compound of Preparation Example 2 was mixed with 9 parts of graphite, 1.5 parts of diaminodicyclohexylmethane and 65 parts of 50% ethanol by mass, and stirred evenly. The mixture was then sprayed on the surface of the substrate and dried in an oven to obtain a composite current collector.
[0113] Preparation Example 3
[0114] Provided is an epoxy resin-flame retardant functional compound, the preparation method of which comprises the following steps:
[0115] Weigh 8 parts of fluorobenzene, 3 parts of concentrated sulfuric acid, and 3 parts of concentrated nitric acid, add them to a container and stir evenly for 60 minutes. Control the temperature to 40°C and the pressure to 3 MPa. Pass argon gas into a closed environment to cause nitration reaction between fluorobenzene and nitric acid to produce a flame retardant material with nitro groups.
[0116] After the flame retardant material with nitro group has completely reacted, the temperature is lowered to room temperature, 24 parts of diphenol propane are weighed and added to the above solution, and stirred for 240 minutes to allow the epoxy groups on the diphenol propane to react with the nitro groups of the flame retardant material with nitro group, so that the molecular chain of the diphenol propane carries the flame retardant material to obtain the epoxy resin-flame retardant functional compound.
[0117] Example 3
[0118] A composite current collector is provided, comprising a current collector substrate and a functional layer disposed on at least one surface of the current collector substrate, wherein the thickness of the functional layer is 3 μm, and the functional layer comprises an adhesive composition, wherein the adhesive composition comprises an epoxy resin-flame retardant functional compound (Preparation Example 3).
[0119] This embodiment also provides a method for preparing the composite current collector, comprising the following steps:
[0120] The epoxy resin-flame retardant functional compound of Preparation Example 3 was mixed with 12 parts of graphite, 2 parts of diaminodicyclohexylmethane and 70 parts of 50% ethanol by mass, and stirred evenly. The mixture was then sprayed on the surface of the substrate and dried in an oven to obtain a composite current collector.
[0121] Preparation Example 4
[0122] Provided is an epoxy resin-flame retardant functional compound, the preparation method of which comprises the following steps:
[0123] Weigh 3 parts of trifluoroaniline, 4 parts of concentrated sulfuric acid, and 5 parts of concentrated nitric acid, add them to a container and stir evenly. Stir for 50 minutes. Control the temperature to 60°C and the pressure to 2.5 MPa. Pass argon gas into a closed environment to cause nitration reaction between fluorobenzene and nitric acid to produce a flame retardant material with nitro groups.
[0124] After the flame retardant material with nitro groups has completely reacted, the temperature is lowered to room temperature, 10 parts of bisphenol diglycidyl ester is weighed and added to the above solution, and stirred for 200 minutes to allow the epoxy groups on the bisphenol diglycidyl ester to react with the nitro groups of the flame retardant material with nitro groups, so that the flame retardant material is attached to the molecular chain of the bisphenol diglycidyl ester to obtain an epoxy resin-flame retardant functional compound.
[0125] Example 4
[0126] A composite current collector is provided, comprising a current collector substrate and a functional layer disposed on at least one surface of the current collector substrate, wherein the thickness of the functional layer is 1.5 μm, and the functional layer comprises an adhesive composition, wherein the adhesive composition comprises an epoxy resin-flame retardant functional compound (Preparation Example 4).
[0127] This embodiment also provides a method for preparing the composite current collector, comprising the following steps:
[0128] The epoxy resin-flame retardant functional compound of Preparation Example 4 was mixed with 10 parts of Super P, 1 part of triethylene glycol amine and 60 parts of 50% ethanol by mass, and then coated on the surface of the substrate by a spraying method and dried in an oven to obtain a composite current collector.
[0129] Example 5
[0130] A composite current collector is provided, which differs from Example 1 in that the thickness of the functional layer is 0.5 μm.
[0131] Example 6
[0132] A composite current collector is provided, which differs from Example 1 in that the thickness of the functional layer is 3.5 μm.
[0133] Example 7
[0134] A composite current collector is provided, which differs from Example 1 in that, in its preparation method, the epoxy resin-flame retardant functional compound of Preparation Example 1 is replaced by an epoxy resin-flame retardant functional compound prepared by the following method:
[0135] Compared with Preparation Example 1, the added amount of bisphenol diglycidyl ester was changed from 10 parts to 9 parts.
[0136] Example 8
[0137] A composite current collector is provided, which differs from Example 1 in that, in its preparation method, the epoxy resin-flame retardant functional compound of Preparation Example 1 is replaced by an epoxy resin-flame retardant functional compound prepared by the following method:
[0138] Compared with Preparation Example 1, the added amount of bisphenol diglycidyl ester was changed from 10 parts to 25 parts.
[0139] Comparative Example 1
[0140] A composite current collector is provided, which differs from Example 1 in that, in its preparation method, the epoxy resin-flame retardant functional compound of Preparation Example 1 is replaced by an epoxy resin-flame retardant functional compound prepared by the following method:
[0141] Compared with Preparation Example 1, no bisphenol diglycidyl ester was added.
[0142] Comparative Example 2
[0143] A composite current collector is provided, which differs from Example 1 in that, in its preparation method, the epoxy resin-flame retardant functional compound of Preparation Example 1 is replaced by an epoxy resin-flame retardant functional compound prepared by the following method:
[0144] Compared with Preparation Example 1, no fluorinated benzene was added.
[0145] Comparative Example 3
[0146] A composite current collector is provided, which differs from Example 1 in that, in its preparation method, the epoxy resin-flame retardant functional compound of Preparation Example 1 is replaced by an epoxy resin-flame retardant functional compound prepared by the following method:
[0147] Compared with Preparation Example 1, bisphenol diglycidyl ester and fluorobenzene were not added.
[0148] Comparative Example 4
[0149] A composite current collector is provided, which differs from Example 1 in that, in its preparation method, the epoxy resin-flame retardant functional compound of Preparation Example 1 is replaced by an epoxy resin-flame retardant functional compound prepared by the following method:
[0150] Compared with Preparation Example 1, bisphenol diglycidyl ester and fluorobenzene are directly mixed without undergoing nitration reaction.
[0151] Comparative Example 5
[0152] A composite current collector is provided. The difference from Example 1 is that the thickness of the functional layer is 3 μm. Moreover, in the preparation method thereof, the epoxy resin-flame retardant functional compound of Preparation Example 1 is replaced with an epoxy resin-flame retardant functional compound prepared by the following method:
[0153] Compared with Preparation Example 1, bisphenol diglycidyl ester and fluorobenzene are directly mixed without undergoing nitration reaction.
[0154] The negative electrode sheet was prepared using the current collectors provided in Examples 1-8 and Comparative Examples 1-5. The preparation method is as follows:
[0155] Hard carbon, conductive carbon black Super P, binder cellulose acetate butyrate and CMC were mixed in a mass ratio of 95:2:2:1 with an appropriate amount of deionized water to prepare a negative electrode slurry, which was then coated on aluminum foil, air-dried at 90°C, and cold-pressed and cut into negative electrode sheets.
[0156] Peel strength test: At room temperature, the negative electrode sheet was cut into a size of width × length = 25 mm × 50 mm, and the peel strength test was performed using a stretching machine and heated to 180°C for stretching.
[0157] Assembling the battery cells:
[0158] Preparation of positive electrode sheets: Sodium nickel chromium manganate, conductive carbon black SP, positive electrode binder PVCF were mixed in a mass ratio of 95:2:3 with an appropriate amount of NMP to prepare a negative electrode slurry. The slurry was coated on copper foil, dried with forced air at 100°C, and cold pressed to form negative electrode sheets.
[0159] Battery preparation: The positive electrode sheet, separator, and negative electrode sheet are wound into a core, with the separator completely covering the positive and negative electrodes. This core is then placed in a metal casing or wrapped in aluminum-plastic film, and the electrolyte is injected. Finally, a series of processes, including resting, formation, and capacity separation, complete the sodium-ion battery.
[0160] Hi-pot test: After winding, the cells are hot-pressed at 6T, 90°C, and 45 seconds. 500 cells are tested at 200V for 5 seconds. A Hi-pot test result of 5-9995MΩ is considered acceptable.
[0161] The test results are shown in Table 1.
[0162] Table 1 Parameters and results of Examples and Comparative Examples
[0163]
[0164]
[0165] As can be seen from Table 1, the present invention introduces an epoxy resin-flame retardant functional compound into the functional layer and uses the functional layer to modify the current collector substrate, which can greatly improve the adhesion between the current collector and the active layer and improve the peeling force of the negative electrode. Moreover, the flame retardant component in the epoxy resin-flame retardant functional compound has flame retardancy, which can prevent the foil from melting and causing safety problems when the battery cell fails. Comparative Examples 1-3 use a single epoxy resin or flame retardant material, which results in poor peeling force compared to epoxy resin-flame retardant functional compound, and the Hi-pot test failure rate of Comparative Examples 1 and 3 is increased compared to Examples 1-8. Comparative Examples 4-5 use a mixture of epoxy resin and flame retardant material, rather than epoxy resin-flame retardant functional compound, which has limited improvement in adhesion, and the Hi-pot test failure rate of Comparative Examples 4-5 is increased compared to Examples 1-8.
[0166] Furthermore, fluorobenzene has a certain lubricity, which can optimize the lubricity of the adhesive composition and prevent the surface of the active layer from being too rough, thereby having better processing performance. For example, if the surface of the active layer is too rough, it will easily lead to wrinkling of the electrode due to the roughness of the electrode during the winding process of the battery cell.
[0167] A comparison of Example 1 with Examples 5-6 shows that if the thickness of the functional layer is too small, it will be detrimental to the process and easily lead to thickness fluctuations, which in turn reduces the peeling force between the current collector and the active layer. If the thickness of the functional layer is too large, the peeling force will be reduced, powder will easily fall off, and the Hi-pot test failure rate will increase, which is not conducive to high capacity and high energy density of the battery. The preferred thickness range is 1μm-3μm.
[0168] By comparing Example 1 with Examples 7-8, it can be seen that if there is too little epoxy resin, the effect of the functional layer will be attenuated, the peeling force between the current collector and the active layer will decrease, and the Hi-pot test failure rate will increase; if there is too much epoxy resin, although the peeling force will increase, it will help to reduce the Hi-pot test failure rate, but too much epoxy resin will cause the electrode to wrinkle, which is not conducive to battery cell preparation.
[0169] The applicant states that the present invention is intended to illustrate the detailed methods of the present invention through the above-described embodiments, but the present invention is not limited to the above-described detailed methods, that is, it does not mean that the present invention must rely on the above-described detailed methods in order to be implemented. Those skilled in the art should understand that any improvements to the present invention, equivalent substitutions for various raw materials in the products of the present invention, addition of auxiliary ingredients, and selection of specific methods, etc., are all within the scope of protection and disclosure of the present invention.
Claims
1. A composite current collector, characterized in that: The composite current collector comprises a current collector substrate and a functional layer disposed on at least one side of the current collector substrate. The functional layer comprises a binder composition, and the binder composition comprises an epoxy resin-flame retardant functional compound.
2. The composite current collector according to claim 1, characterized in that: The epoxy resin-flame retardant functional compound is an epoxy resin-fluorobenzene compound.
3. The composite current collector according to claim 1 or 2, characterized in that: The thickness of the functional layer is 1 μm to 3 μm.
4. A method for preparing a composite current collector according to any one of claims 1 to 3, characterized in that: The preparation method comprises the following steps: (1) After introducing nitro groups into the flame retardant material, a flame retardant material having nitro groups is obtained, and the flame retardant material having nitro groups is mixed with an epoxy resin and subjected to an esterification reaction to obtain a binder composition; (2) mixing the binder composition with a curing agent and a solvent to obtain a functional slurry; (3) The functional slurry is coated on the surface of a current collector substrate and dried to obtain a composite current collector.
5. The preparation method according to claim 4, characterized in that: The epoxy resin in step (1) comprises at least one of bisphenol diglycidyl ester, diphenol propane and polyphenol type glycidyl ester; Preferably, the flame retardant material in step (1) comprises a fluorobenzene compound; Preferably, the fluorobenzene compound includes at least one of fluorobenzene, difluoroaniline, trifluoroaniline and tetrafluorophenol.
6. The preparation method according to claim 4 or 5, characterized in that: The method of introducing nitro groups into the flame retardant material in step (1) is: mixing the flame retardant material, a catalyst and concentrated nitric acid to allow the flame retardant material to undergo a nitration reaction with the nitric acid; Preferably, the nitration reaction is accompanied by stirring; Preferably, the flame retardant material, the catalyst and the concentrated nitric acid are mixed for 30 to 60 minutes; Preferably, the temperature of the nitration reaction is 40°C to 70°C; Preferably, the pressure of the nitration reaction is controlled within the range of 1 MPa to 3 MPa; Preferably, the catalyst comprises concentrated sulfuric acid; Preferably, the mass ratio of the flame retardant material, the catalyst and concentrated nitric acid is (3-8):(3-8):(3-8).
7. The preparation method according to any one of claims 4 to 6, characterized in that: In step (2), the material used to be mixed with the binder composition also includes a conductive agent; The content of each material is as follows:
8. The preparation method according to claim 7, characterized in that: The curing agent comprises at least one of diaminodicyclohexylmethane, triethylene glycol amine, boron trifluoride glycerol and boron trifluoride aniline; Preferably, the conductive agent comprises at least one of graphite, Super P, carbon nanotubes, acetylene black and Ketjen black; Preferably, the solvent comprises at least one of alcohol, water, acetone, NMP, ethyl ester, and 50% ethanol; Preferably, the alcohol comprises methanol and / or ethanol; Preferably, the mass fraction of the alcohol is 40% to 60%.
9. A negative electrode sheet, characterized in that: The negative electrode sheet comprises a current collector and an active layer disposed on at least one side of the current collector, wherein the current collector is a composite current collector according to claim 1 or 2, or a composite current collector prepared by the method according to any one of claims 3 to 8; preferably, the active layer comprises a negative electrode active material, and the negative electrode active material comprises hard carbon; Preferably, the peeling force of the negative electrode sheet is greater than 0.8N.
10. A battery, characterized in that: The battery comprises the negative electrode sheet according to claim 9; Preferably, the battery is a sodium ion battery.
Citation Information
Patent Citations
Flame-retardant additives
CN102015869A
Negative electrode for lithium metal battery, method for manufacturing same, and lithium metal battery comprising same
CN111801816A
Composite current collector and preparation method thereof
CN114583180A
Heat-resistant carbon-coated aluminum foil of power battery current collector and preparation method of heat-resistant carbon-coated aluminum foil
CN115000413A
Prime coating slurry, positive plate, battery cell and preparation method thereof
CN116230950A